A Review of Hybrid Exploratory Testing Techniques - Yogi, Manas kumar; Jnapika, Y; Ped, Bhanuprakash (International Journal of Computer Sciences and Engineering, 2019)
Wildcat testing contains a mess of strategy related to it. It is a decent combination of structured thinking and race exploration that may be terribly powerful for locating bugs and substantiate correctness. This paper shows however the wildcat testing mentality is often combined with additional ancient scenario-based and scripted testing. This hybrid technique relaxes a lot of the rigidity unremarkably related to scripting and makes smart use of the wildcat testing steering bestowed. It additionally permits groups that square measure heavily unconditional in existing scripts to feature wildcat testing to their arsenal. Ancient state of affairs testing is incredibly seemingly to be a well-known idea for the reader. Several testers write or follow some type of script or end-to-end state of affairs once they perform manual testing. State of affairs testing is well-liked as a result of it lends confidence that the merchandise can faithfully perform the state of affairs for actual users. The additional the state of affairs reflects expected usage, the additional such confidence is gained. The additional part that wildcat testing lends to the current method is to inject variation into the state of affairs in order that a wider swath of the merchandise gets tested. Users can't be unnatural to merely execute the software package the manner we have a tendency to intend, therefore our testing ought to expand to hide these extra state of affairs variants.